2020
DOI: 10.1002/advs.202002253
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Modulations of Tumor Vasculature and Stromal Barriers Augment the Active Targeting Efficacy of Antibody‐Modified Nanophotosensitizer in Desmoplastic Ovarian Carcinoma

Abstract: Active‐targeted nanoparticles are attractive carriers due to their potentials to facilitate specific delivery of drugs into tumor cells while sparing normal cells. However, the therapeutic outcomes of active‐targeted nanomedicines are hampered by the multiple physiological barriers in the tumor microenvironment (TME). Herein, an epidermal growth factor receptor‐targeted ultra‐pH‐sensitive nanophotosensitizer is fabricated, and the regulation of the TME to augment the active targeting ability and therapeutic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 45 publications
0
40
0
Order By: Relevance
“…To evaluate the 1 O 2 responsivity of SPR-SOSG, the Ce6-conjugated micellar nanophotosensitizer (UPS-Ce6) was applied as an 1 O 2 nanogenerator. 37 Compared with the slight enhancement at the nanoparticle state (pH 7.4), SPR-SOSG exhibited a rapid increment in the fluorescence of SOSG at the disassembled state (pH 5.4) in response to the photosensitized singlet oxygen (Figure 2E). The 1 O 2 sensing capacity was also verified by the optical imaging study, as shown in Figure 2F.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate the 1 O 2 responsivity of SPR-SOSG, the Ce6-conjugated micellar nanophotosensitizer (UPS-Ce6) was applied as an 1 O 2 nanogenerator. 37 Compared with the slight enhancement at the nanoparticle state (pH 7.4), SPR-SOSG exhibited a rapid increment in the fluorescence of SOSG at the disassembled state (pH 5.4) in response to the photosensitized singlet oxygen (Figure 2E). The 1 O 2 sensing capacity was also verified by the optical imaging study, as shown in Figure 2F.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To conceptually differentiate 1 O 2 in diverse endocytic organelles, the early endosome-targeted ( ee SPR-SOSG), late endosome-targeted ( le SPR-SOSG), and lysosome-targeted ( ly SPR-SOSG) nanosensors were formulated and extensively investigated (Figure S1). The photosensitizer chlorin e6 (Ce6)-conjugated UPS micelles (UPS-Ce6) were involved as nanogenerators of 1 O 2 . We comprehensively characterized the 1 O 2 imaging efficacy of SPR-SOSG and the in situ visualization of 1 O 2 within specific endocytic organelles in living cells and 4T1 tumor-bearing animals, as well as prediction capacity of the therapeutic response of PDT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 14 Even with the incorporation of active targeting moieties, cellular uptake in PDAC deep tissues still faces the substantial barrier of nanoparticle internalization only within the first few layers of tumor cells (proximal to the vasculature). 15 17 To date, a paramount challenge is in the search for intelligent nanotheranostics for such hypopermeable tumors, especially in breaking the PDAC-specific physical barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complex tumor microenvironment, only a part of the nanoparticles (NPs) that accumulated at the tumor sites can be endocytosed into tumor cells 7 , and the other NPs are all sequestered in the extracellular regions. Given that most known drug targets (e.g., DNA and microtubule) are located in the intracellular compartments, the therapeutic outcomes of nanomedicines greatly depend on cellular internalization efficiency rather than tumor accumulation [8][9][10] .…”
mentioning
confidence: 99%